Proceedings of the 17th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2014
DOI: 10.1145/2531602.2531641
|View full text |Cite
|
Sign up to set email alerts
|

Tracking serendipitous interactions

Abstract: In many creative work environments, serendipitous interactions between members of different groups may lead to enhanced productivity, collaboration and knowledge dissemination. Two factors that may have an influence on such interactions are cultural differences between individuals in highly multicultural workplaces, and the layout and physical spaces of the workplace itself. In this work, we investigate how these two factors may facilitate or hinder inter-group interactions in the workplace. We analyze traces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Finally , our study is limited to a single Western European country. Because the identified antecedents of serendipity may vary by cultural context, we could assume that serendipity and its outcomes are also culture‐specific to a certain degree (Brown et al, ). Comparative studies could shed light on the cultural contingency of serendipity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally , our study is limited to a single Western European country. Because the identified antecedents of serendipity may vary by cultural context, we could assume that serendipity and its outcomes are also culture‐specific to a certain degree (Brown et al, ). Comparative studies could shed light on the cultural contingency of serendipity.…”
Section: Discussionmentioning
confidence: 99%
“…We propose a positive effect of self‐disclosure on online serendipity because providing personal information to online services allows for richer web experiences, thereby enhancing the likelihood of serendipitous encounters. Examinations of serendipity in an offline context have stressed the importance of social interactions for serendipity experiences (e.g., Brown, Efstratiou, Leontiadis, Quercia, & Mascolo, ). Applied to the online context, higher levels of online self‐disclosure can be assumed to facilitate social connections and exchange on the Internet (e.g., in social media).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Bluetooth-based systems for example can rely on widespread adoption but are usually power hungry and do not offer fine grained data [8], [9], [10], [6]. On the other hand, systems based on custom built devices can provide fine granularity but require dedicated hardware which hinder adoption [11], [12], [13]. The recent interest in wearable devices [14] has brought us to question if those devices are able to fulfill both needs.…”
Section: Introductionmentioning
confidence: 99%
“…Taylor et al [52] identified that the home should support the smartness (meaning intelligence) of its occupants, though in the work context 'smartness' will have different meanings, including e.g. fostering social interactions [13]. We need to shift the rhetoric of smartness away from automation back towards the human, so that smart buildings can be smart for occupants, too, not just building managers.…”
Section: Hbi's Role In Supporting (Or Challenging) the Status Quomentioning
confidence: 99%